(untitled) (Economics and region, 2024)
The article systematizes the theoretical and methodological foundations of the application of analytical procedures in the audit of the financial and economic activity of agrarian formations. Analytical procedures are considered as a set of actions of the auditor, aimed at identifying the causes of deviations between actual and expected indicators, at establishing the relationship between financial and non-financial data, as well as trends of changes in economic activity. Attention is focused on the fact that the content and scope of analytical procedures in the audit of the financial and economic activity of agrarian formations are influenced by the specifics of agricultural production, the types and volumes of activity of a specific business entity, the forms and accounting systems, the features of electronic data processing, the specifics of the construction of the internal control system and analysis. It has been established that analytical procedures are classified by scope of application, stages of audit, purpose of results and frequency of their use, and scientists define the scope of use of such procedures in audit in different ways. Analytical procedures in the audit of agrarian formations have a wide range of use at the initial (organizational) stage, when collecting evidence (direct audit), as well as at the final stage of the audit. The staged audit before and after the reporting of agricultural formations is aimed at improving the accounting and reporting system. It has been proven that it is not correct to reduce the performance of analytical procedures to the determination of a set of coefficients or comparisons with the auditor’s calculations, since the essence of analytical procedures should primarily be manifested in establishing relationships, identifying the causes of deviations and development trends. It is recommended not to limit analytical procedures to the framework of checking financial statements, to study analytical procedures as a component of audit procedures taking into account the interrelationship of the concepts "reception" - "method" - "procedure", taking into account that audit evidence for the formation of an audit report is collected on the basis of taking into account the connection between audit methods and procedures. To increase the effectiveness of the audit, it is recommended to perform analytical procedures in essence, focusing on areas of increased risk, before testing the details.